Junctional Adhesion Molecule: An Expression in Human Endometrial Carcinoma. Issue 2 (1st January 2009) - Koshiba, Hisato; Hosokawa, Kenichi; Kubo, Akiko; Tokumitsu, Norimasa; Watanabe, Ai; Honjo, Hideo
Abstract : Junctional adhesion molecule A (JAM-A) is involved in cell-cell contact and tight junction formation. Loss of cell adhesion molecules may be associated with high histologic grade and invasiveness of endometrial carcinoma. We attempted to determine JAM-A expression in human endometrial carcinoma and its correlations with pathologic features, stage, and survival. Junctional adhesion molecule A expression in human endometrial carcinoma was evaluated by immunohistochemistry. In addition, we cultured human well and poorly differentiated endometrial adenocarcinoma cell lines, Ishikawa cells, and KLE in 3-dimensional basement membrane preparation, and JAM-A expression in these cells was assessed by real-time reverse transcription-polymerase chain reaction and immunohistochemistry. Junctional adhesion molecule A immunostaining intensity was negatively correlated with histologic grade ( τ = −0.420, P < 0.0001), myometrial invasion ( τ = −0.306, P < 0.01), and stage ( τ = −0.383, P < 0.0001). Low JAM-A immunostaining intensity was associated with positive vascular space involvement ( P < 0.01). Moreover, low immunostain intensity was significantly ( P < 0.0001) related to low overall survival rate and progression-free survival rate. Additionally, in our 3-dimensional epithelial cell culture, JAM-A expression in poorly differentiated adenocarcinoma was significantly lower than that in well-differentiated adenocarcinoma ( P < 0.001). Junctional adhesion molecule A expression seems to be reduced in high-grade or advanced endometrial carcinoma and may be a prognostic factor.